Cytokine Changes in the Nasal Fluid after Acute Acoustic Trauma: Nasal Cytokine Response to Acoustic Trauma - Jovanović, Vanja; Marjanović, Sonja; Perić, Aleksandar; Jovanović, Dejan; Radojičić, Zoran; Đukić, Mirjana; Vojvodić, Danilo (Journal of Medical Biochemistry, 2025)
AbstractBackground: Occupational noise-induced hearing loss poses a significant health risk especially for military and low enforcement. Unlike steady, prolonged noise, impulse noise, such as gunfire, lead to more immediate and severe hearing impairment. This study explores the link between sensorineural hearing loss and cytokine levels in nasal secretions of male and female military cadets exposed to high-intensity gunfire noise.Methods: 105 cadets (75 males and 30 females, aged 19–25) undergoing regular firearms training were included. Audiometric testing and measurement of IL-1β, TNF-α, GM-CSF, and IL-10 concentrations in nasal secretions were conducted at three-time points: 24 hours before, immediately after and 24 hours following noise exposure. Results: Acute acoustic trauma affected the hearing of 39% of male and 21% of female participants. Among those with audiometric changes, IL-1β levels increased immediately after exposure, while both IL-1β and GM-CSF levels were elevated 24 hours later. Nasal IL-1β and GM-CSF levels significantly changed across all participants, with the most pronounced alterations seen in those with audiogram changes. Male cadets exhibited higher values of pro-inflammatory/anti-inflammatory cytokine ratios compared to female cadets.Conclusions: Acoustic trauma associated with a certain degree of hearing loss due to noise exposure is linked to an increase in nasal pro-inflammatory cytokine levels, and this effect is more pronounced in men than in women.
Keywords: Audiometry; Cytokines; Gunfire; Gender; Hearing loss; Impulse noise; Interleukin-1β; Nasal cavity